More research, better books? A structural equation model and content evaluation of drama textbooks in Indonesian higher education - Pamungkas, Onok Yayang; Hanun, Farida; Paresti, Suci; Agung, Iskandar; Ma'rifataini, Lisa´diyah; Mastiyah, Iyoh; Sudiyono; Suhanah (Research Journal in Advanced Humanities, 2025)
This study aims to examine the relationship between research-based learning, institutional support, and lecturers’ research productivity in relation to the quality of drama textbooks produced within Indonesian teacher education institutions (TEIs). Employing a mixed-methods approach that integrates Structural Equation Modeling (SEM) with content and visual-physical textbook evaluation, the findings reveal that institutional support serves as a critical mediating factor between pedagogical strategies and research output. Despite increased research productivity, the translation of scholarly work into high-quality textbooks remains limited, both in terms of content richness and visual engagement. The analysis highlights a structural disconnection between academic research and the development of pedagogically sound educational media, with minimal integration of technological and multimodal elements. This study proposes a conceptual model that integrates academic productivity pathways with pedagogical translation mechanisms, offering a holistic framework for the development of research-informed teaching materials. The findings contribute theoretically to the validation of a research productivity model and advance a new conceptualization of how academic research can be transformed into impactful learning resources. Practical implications are drawn for higher education policy in the fields of arts, humanities, and teacher preparation.